Examining the Role of YouTube Creators in Promoting Emerging Tourism Destinations in Indonesia - Siti Anindya Lestari (Bali Tourism Board, 2026)
The rapid expansion of digital media has fundamentally transformed tourism marketing, positioning social media creators as influential actors in shaping destination awareness and travel behavior. Among various digital platforms, YouTube has emerged as a powerful medium for promoting tourism destinations through immersive visual storytelling, authentic travel experiences, and interactive audience engagement. This study examines the role of YouTube creators in promoting emerging tourism destinations in Indonesia, with particular emphasis on their contributions to destination image formation, cultural representation, and tourism motivation. Employing a qualitative research approach, the study utilizes content analysis supported by a systematic review of contemporary literature published between 2020 and 2026 on digital tourism marketing, destination branding, influencer communication, and travel vlogging. The analysis is structured around three dimensions: visual representation, narrative representation, and audience engagement. The findings indicate that YouTube creators play a significant role as destination image builders by presenting immersive visual content that enhances the visibility and attractiveness of emerging destinations such as Labuan Bajo, Likupang, Wakatobi, Sumba, and Lake Toba. Authentic storytelling and firsthand travel experiences strengthen viewers' trust while simultaneously communicating local culture, traditions, and community identity. Furthermore, parasocial relationships between creators and audiences increase destination credibility and positively influence travel intentions. The study also identifies YouTube creators as informal digital ambassadors who contribute to destination branding, tourism diversification, and regional tourism development. However, issues related to cultural commodification, stereotypical representation, and commercialization require greater attention to ensure ethical and sustainable tourism promotion. The study concludes that strategic collaboration among tourism authorities, local communities, and YouTube creators can strengthen sustainable destination marketing while encouraging responsible tourism practices and enhancing the global competitiveness of Indonesia's emerging tourism destinations.